Effects of Housing Types on Cecal Microbiota of Two Different Strains of Laying Hens During the Late Production Phase - Adhikari, Bishnu; Jun, Se-Ran; Kwon, Young M.; Kiess, Aaron S.; Adhikari, Pratima (Frontiers in Veterinary Science, 2020)
Due to animal welfare issues, European Union has banned the use of conventional cages (CC) and non-EU countries including the US are also under constant public pressure to restrict their use in egg production. Very limited information is available on the composition of the microbial community of hens raised in different housing environments. This study was conducted to determine the effects of CC and enriched colony cages (EC) on cecal microbiota of two commercial laying hen strains, Hy-Line W36 (WL) and Hy-Line Brown (HB) during the late production stage (53, 58, 67, and 72 wks of age). Cecal microbiota was studied by analyzing 16S rRNA gene sequences with QIIME2 ver. 2018.8. Differentially abundant taxa were identified by LEfSe (P<0.05, LDA score>2.0) analysis. At phylum level, Actinobacteria was significantly enriched in WL at all time points while Synergistetes (53 wks), Spirochaetes (58 wks), and Synergistetes and Spirochaetes (67 wks) were significantly higher in HB. At genus level, Bifidobacterium (at all time points) and butyric acid producing genera such as Butyricicoccus and Subdoligranulum (58 and 72 wks) were significantly higher in WL as compared to HB. Moreover, Proteobacteria (72 wks) and its associated genus Campylobacter (67 and 72 wks) were significantly enriched in EC as compared to CC. Alpha diversity was significantly higher in HB (at all time points) and in EC (67 weeks) as compared to WL and CC, respectively. Similarly, there was a significant difference in community structure (beta diversity) between WL and HB (all time points) as well as between EC and CC (67 wks). The effect of housing and strains not only seen at the bacterial composition and structure but also reflected at their functional level. In sum, cecal microbiota composition, diversities, and their functional pathways were affected by housing type which further varied between two commercial laying hen strains, HB and WL. This suggests that both housing and genetic strains of laying hens should be considered for selection of the alternative housing systems such as enriched colony cage.